Circuits of Capital and Transnational Corporate Spatial Behaviour: Nestlé in Southeast Asia - Bill Pritchard, Bill; Fagan, Robert (The International Journal of Sociology of Agriculture and Food, 2021)
The spatial behaviour of transnational corporations cannot be rendered as a monolithic 'whole'. Individual transnational corporations exercise a range of spatial strategies at varying scales. A key problem for economic sociology and human geography is how to represent the diversity that constitutes corporate spatial behaviour. Through the circuits of capital model, this article suggests that corporate spatial behaviour can be understood as manifested through circuits of capital production, realisation and reproduction. This approach is employed to help understand the spatial behaviour of Nestlé in Southeast Asia. This case illustrates the complex, and at times contradictory, interplay of strategies that can co-exist within the single corporation. The article concludes by presenting an agenda for future research, based around the need to more fully comprehend the linkages between Nestlé's legal-corporate existence in the region, and its production and sales strategies.